Transcriptome analysis revealed the role of moderate exogenous methyl jasmonate treatments in enhancing the metabolic pathway of L-borneol in the Blumea balsamifera - Guan, Lingliang; Lin, Na; Wan, Lingyun; Yu, Fulai; Chen, Xiaolu; Xie, Xiaoli; Yuan, Chao; Soaud, Salma A.; Abd Elhamid, Mohamed A.; Heakel, Rania M. Y.; Wang, Linghui; El-Sappah, Ahmed H. (Frontiers in Plant Science, 2024)
Blumea balsamifera L. (Ainaxiang) DC. is a perennial herb of the compositae family. It's also the primary source of natural borneol. Endo-borneol, the principal medical active element in B. balsamifera, is anti-inflammatory, antioxidant, analgesic, enhances medicine absorption, and refreshes, as well as a spice and cosmetic. Industrialization of B. balsamifera is limited by its low L-borneol concentration. Thus, understanding the accumulation pattern of the secondary metabolite endo-borneol and its synthesis process in secondary metabolism is critical for increasing B. balsamifera active ingredient content and cultivation efficiency. In this work, B. balsamifera was treated with varying concentrations (1.00 and 10.00 mmol/L) of methyl jasmonate (MeJA) as an exogenous foliar activator. The physiological parameters and L-borneol concentration were then assessed. Transcriptome sequencing of B. balsamifera-induced leaves was used to identify key genes for monoterpene synthesis. The treatment effect of 1mmol/L MeJA was the best, and the leaves of all three leaf positions accumulated the highest L-borneol after 120 hours, correspondingly 3.043, 3.346, and 2.044 mg•g -1 FW, with significant differences from the control. The main assembly produced 509,285 transcripts with min and max lengths of 201 and 23,172, respectively. DEG analysis employing volcano blots revealed 593, 224, 612, 2405, 1353, and 921 upregulated genes and 4, 123, 573, 1745, 766, and 763 downregulated genes in the treatments D1_1vsCK, D1_10vsCK, D2_1vsCK, D2_10vsCK, D5_1vsCK, and D5_10vsCK. Interestingly, when exposed to MeJA treatments, the MEP pathway's unigenes express themselves more than those of the MVA route. Finally, when treated with 1 mmol/L, the genes DXR, DXS, and GPS showed increased expression over time. At the same time, a 10 mmol/L therapy resulted in elevated levels of ispH and GGPS.